2016
DOI: 10.9769/epj.2016.8.2.lg
|View full text |Cite
|
Sign up to set email alerts
|

EFT (Emotional Freedom Techniques) Remediates PTSD and Psychological Symptoms in Veterans: A Randomized Controlled Replication Trial

Abstract: Posttraumatic stress disorder (PTSD) is a common condition among veterans and is often regarded as treatment-resistant. Emotional Freedom Techniques (EFT) combines brief exposure therapy with acupressure and has demonstrated efficacy for PTSD in other trials and meta-analyses. This study recruited 58 veterans who scored 50 or greater on the military PTSD checklist (PCL-M), indicating clinical symptom levels. Participants were randomized into a Treatment As Usual (TAU) wait-list group (n = 26) and an experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
(54 reference statements)
2
18
0
Order By: Relevance
“…6 Although at the end of 6 sessions, his PCL-M score of 40 was not as low as the mean scores of the combined EFT and control groups, which had declined to a mean of 34 (-52%; P < 0.001), his scores continued to drop as he continued to tap and move on with his life. The mean score of 34 was maintained at the 3-and 6-month follow-up points for the Veterans in the study, whereas his scores dropped to 22 at the 6-month follow-up date.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…6 Although at the end of 6 sessions, his PCL-M score of 40 was not as low as the mean scores of the combined EFT and control groups, which had declined to a mean of 34 (-52%; P < 0.001), his scores continued to drop as he continued to tap and move on with his life. The mean score of 34 was maintained at the 3-and 6-month follow-up points for the Veterans in the study, whereas his scores dropped to 22 at the 6-month follow-up date.…”
Section: Discussionmentioning
confidence: 86%
“…The replication study 6 used the same measures as in the first study, 4 which have been shown to be valid and reliable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After six months 80% of veterans treated no longer met criteria for PTSD. Geronilla et al [19] replicated the 2013 Church study. 96% of the EFT treated group no longer met the criteria for PTSD and the symptom reduction maintained at 3 and 6-month follow-up.…”
Section: Research On Eftmentioning
confidence: 93%